UNISH SHATAK, ‘PATHER PANCHALI’ EBONG KATHAK HARIHAR ROY-ER OPOMRITYU/ উনিশ শতক, ‘পথের পাঁচালী’ এবং কথক হরিহর রায়ের অপমৃত্যু (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
Nineteenth century was the turning period for the Bengal’s socio-cultural construct and establishment. It was also the time when mediaeval economic layout of Bengal took a hit and it turned into a new kind of feudalism thanks to the Permanent Settlement Rule passed by the then East India Company in 1793. Due to this economic transformation, city of Calcutta emerged as the newly settled conurbation of the state with the illumination of renaissance. Consequently all the prior affluent townships from Islamic reign like Berhampur, Murshidabad, Burdwan or Krishnanagar were compelled to get the backseat. These economic and political swaps also commuted the local people’s understanding of social celebrations and rituals. Due to colonial education system and Victorian refinements, the cultural aspects of Calcutta and surroundings were briskly changed. The artists who were attached to old customs and practices started to get affected by this conveyance. Writer Bibhutibhusan Bandyopadhyay in his all-time classic ‘Pather Panchali’ (1929) tried to catch this Cultural transitions and the dilemma of an artist through the focal point of Harihar Roy. Harihar was father of Apu, the main protagonist of the novel. By his job description, Harihar was a ‘Kathak’ (kind of reciter). He usually performed some selected parts from the old texts like Puranas, Bhagabata, Chandi-kavya and Mangal-Kavya. His consumers were by and large wealthy families from rural Bengal. But the new wave of cultural changes in Calcutta started to overpower Harihar’s line of work and job insecurity commenced to appear as the looming threat. In this article we will try to observe this particular cultural shock, changes and historical turn-arounds through the case of Harihar.
Keywords: 19th century Bengal; Economic and cultural shifting; Renaissance; land reformation; Emergence of city of Calcutta